Patterns of Insect Abundance and Distribution in Urban Domestic Gardens in Bangalore, India - Madhumitha Jaganmohan; Lionel Sujay Vailshery; Harini Nagendra (Diversity, 2013)
Domestic gardens may play a vital role in supporting urban insect biodiversity, despite their small size. This paper assesses the abundance, diversity and distribution of insects in urban domestic gardens in the tropics, through a study in the rapidly expanding Indian city of Bangalore. Fifty domestic gardens were studied using a combination of light traps and pitfall traps. We recorded a large number of insects, 2,185 insects from 10 orders, of which ants, bugs, beetles and flies were the most common. We found 25 species of trees (from 160 individuals) and 117 species of herbs and shrubs in the 50 sampled domestic gardens. The number of insect orders encountered was significantly related to the number of tree and herb/shrub species. Garden management practices also influenced the abundance and richness of insect orders. Thus, greater numbers of insects were observed in gardens with a greater proportion of bare soil relative to grass area and with less intensive weeding practices. More insect orders were encountered in gardens with a composting pit. Insect numbers were significantly reduced in gardens subjected to pesticide application. Most residents avoided application of pesticides and herbicides, citing health concerns.